2D Quantitative Imaging of Magnetic Nanoparticles by an AC Biosusceptometry Based Scanning Approach and Inverse Problem - Gabriel Gustavo de Albuquerque Biasotti; Andre Gonçalves Próspero; Marcelo Dante Tacconi Alvarez; Maik Liebl; Leonardo Antonio Pinto; Guilherme Augusto Soares; Andris Figueiroa Bakuzis; Oswaldo Baffa; Frank Wiekhorst; José Ricardo de Arruda Miranda (Sensors, 2021)
The use of magnetic nanoparticles (MNPs) in biomedical applications requires the quantitative knowledge of their quantitative distribution within the body. AC Biosusceptometry (ACB) is a biomagnetic technique recently employed to detect MNPs in vivo by measuring the MNPs response when exposed to an alternate magnetic field. The ACB technique presents some interesting characteristics: non-invasiveness, low operational cost, high portability, and no need for magnetic shielding. ACB conventional methods until now provided only qualitative information about the MNPs’ mapping in small animals. We present a theoretical model and experimentally demonstrate the feasibility of ACB reconstructing 2D quantitative images of MNPs’ distributions. We employed an ACB single-channel scanning approach, measuring at 361 sensor positions, to reconstruct MNPs’ spatial distributions. For this, we established a discrete forward problem and solved the ACB system’s inverse problem. Thus, we were able to determine the positions and quantities of MNPs in a field of view of <semantics>5×5×1<mtext> </mtext>cm3</semantics> with good precision and accuracy. The results show the ACB system’s capabilities to reconstruct the quantitative spatial distribution of MNPs with a spatial resolution better than <semantics>1<mtext> </mtext>cm</semantics>, and a sensitivity of <semantics>1.17<mtext> </mtext>mg</semantics> of MNPs fixed in gypsum. These results show the system’s potential for biomedical application of MNPs in several studies, for example, electrochemical-functionalized MNPs for cancer cell targeting, quantitative sensing, and possibly in vivo imaging.